Fibonacci-like sequences

Conside The Fibonacci sequence is defined by f 1 = 1 , f 2 = 1 , f n = f n 1 + f n 2 for n 3. f_1 = 1, f_2 = 1, f_n = f_{n-1} + f_{n-2} \text{ for } n \geq 3. We have that f 13 = 233. f_{13} = 233. Consider a sequence such that

g 1 = 1 , g 2 = x , g n = g n 1 + g n 2 for n 3. g_1 = 1, g_2 = x, g_n = g_{n-1} + g_{n-2} \text{ for } n \geq 3.

Determine the sum of all positive integer values of x 2 x \geq 2 for which 233 233 is a term of the sequence g g .


The answer is 706.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

7 solutions

Jimmy Kariznov
Sep 1, 2013

Using the recursion, g 3 = x + 1 g_3 = x+1 , g 4 = 2 x + 1 g_4 = 2x+1 , g 5 = 3 x + 2 g_5 = 3x+2 , g 6 = 5 x + 3 g_6 = 5x+3 , g 7 = 8 x + 5 g_7 = 8x+5 , g 8 = 13 x + 8 g_8 = 13x+8 , g 9 = 21 x + 13 g_9 =21x+13 , g 10 = 34 x + 21 g_{10} = 34x+21 , g 11 = 55 x + 34 g_{11} = 55x+34 , and g 12 = 89 x + 55 g_{12} = 89x+55 .

Since g 2 > g 1 > 0 g_2 > g_1 > 0 and g n = g n 1 + g n 2 g_{n} = g_{n-1} + g_{n-2} for n 3 n \ge 3 we can show that g n g_n is a strictly increasing sequence. Then, since x 2 x \ge 2 , we have that g n > g 12 = 89 x + 55 233 g_n > g_{12} = 89x+55 \ge 233 for all n 13 n \ge 13 . So, we only need to find integers x 2 x \ge 2 such that g n = 233 g_n = 233 for some positive integer n 12 n \le 12 .

We have just 12 12 easy cases to check:

g 1 = 1 233 g_1 = 1 \neq 233

g 2 = x = 233 x = 233 g_2 = x = 233 \leadsto x = 233

g 3 = x + 1 = 233 x = 232 g_3 = x+1 = 233 \leadsto x = 232

g 4 = 2 x + 1 = 233 x = 116 g_4 = 2x+1 = 233 \leadsto x = 116

g 5 = 3 x + 2 = 233 x = 77 g_5 = 3x+2 = 233 \leadsto x = 77

g 6 = 5 x + 3 = 233 x = 46 g_6 = 5x+3 = 233 \leadsto x = 46

g 7 = 8 x + 5 = 233 x = 57 2 g_7 = 8x+5 = 233 \leadsto x = \tfrac{57}{2}

g 8 = 13 x + 8 = 233 x = 225 13 g_8 = 13x+8 = 233 \leadsto x = \tfrac{225}{13}

g 9 = 21 x + 13 = 233 x = 220 21 g_9 = 21x+13 = 233 \leadsto x = \tfrac{220}{21}

g 10 = 34 x + 21 = 233 x = 106 17 g_{10} = 34x+21 = 233 \leadsto x = \tfrac{106}{17}

g 11 = 55 x + 34 = 233 x = 199 55 g_{11} = 55x+34 = 233 \leadsto x = \tfrac{199}{55}

g 12 = 89 x + 55 = 233 x = 2 g_{12} = 89x+55 = 233 \leadsto x = 2

Hence, the sum of all positive integers x 2 x \ge 2 such that g n = 233 g_n = 233 for some integer n n is 233 + 232 + 116 + 77 + 46 + 2 = 706 233+232+116+77+46+2 = \boxed{706} .

Is there any way to get this answer without brute forcing it, or at least an explanation as to why the ones that work work? Is it truly just a coincidence?

Michael Tong - 7 years, 9 months ago

Log in to reply

If anyone is still here, how could this problem be approached for numbers larger than 233? Does finding a generalised closed form help?

Arthur Conmy - 4 years, 5 months ago
Jeremy Kong
Sep 1, 2013

Lemma : It is clear that for positive integer n 4 n \geq 4 , g n = f n 3 + f n 2 x g_n = f_{n-3} + f_{n-2}x . Proof : We use strong induction on n n .

Base case - We need to prove this for n = 4 n = 4 and n = 5 n = 5 .

If n = 4 n = 4 , g 4 = g 2 + g 3 = g 2 + ( g 1 + g 2 ) = 1 + 2 x g_4 = g_2 + g_3 = g_2 + (g_1 + g_2) = 1 + 2x . Since f 1 = 1 f_1 = 1 and f 2 = 2 f_2 = 2 , we have g 4 = f 1 + f 2 x g_4 = f_1 + f_2x as required.

If n = 5 n = 5 , g 5 = g 3 + g 4 = ( g 1 + g 2 ) + ( 1 + 2 x ) = 2 + 3 x g_5 = g_3 + g_4 = (g_1 + g_2) + (1 + 2x) = 2 + 3x . Since f 2 = 2 f_2 = 2 , f 3 = 3 f_3 = 3 we have g 5 = f 2 + f 3 x g_5 = f_2 + f_3x as required.

Induction step - For arbitrary k 5 k \geq 5 , we take g k = f k 3 + f k 2 x g_k = f_{k-3} + f_{k-2}x and g k 1 = f k 4 + f k 3 x g_{k-1} = f_{k-4} + f_{k-3}x . We need to show g k + 1 = f k 2 + f k 1 x g_{k+1} = f_{k-2} + f_{k-1}x .

By definition of g g we have g k + 1 = g k + g k 1 g_{k+1} = g_k + g_{k-1} g k + 1 = f k 3 + f k 2 x + f k 4 + f k 3 x g_{k+1} = f_{k-3} + f_{k-2}x + f_{k-4} + f_{k-3}x Refactoring, g k + 1 = ( f k 3 + f k 4 ) + ( f k 2 + f k 3 ) x g_{k+1} = (f_{k-3} + f_{k-4}) + (f_{k-2} + f_{k-3})x By the definition of Fibonacci numbers, we have g k + 1 = f k 2 + f k 1 x g_{k+1} = f_{k-2} + f_{k-1}x as required.

So if the sequence contains 233 233 then for some n n , we will have 233 = f n 3 + f n 2 x 233 = f_{n-3} + f_{n-2}x . Then, for n 4 n \geq 4 by the lemma we have x = 233 f n 3 f n 2 x = \frac{233 - f_{n-3}}{f_{n-2}} The first 12 12 terms of the Fibonacci sequence are ( 1 , 2 , 3 , 5 , 8 , 13 , 21 , 34 , 55 , 89 , 144 , 233 ) (1, 2, 3, 5, 8, 13, 21, 34, 55, 89, 144, 233) - clearly since x x is a positive integer we need not be concerned with the cases where f n 3 233 f_{n-3} \geq 233 . Checking each pair of consecutive terms gives us the values x = 2 , 46 , 77 , 116 x = 2, 46, 77, 116 But our equation only applied for n 4 n \geq 4 - we observe that it is also possible that g 2 g_2 or g 3 g_3 could be 233 233 . If g 2 = 233 g_2 = 233 then x = 233 x = 233 ; if g 3 = 233 g_3 = 233 then we have 1 + x = 233 1 + x = 233 and x = 232 x = 232 . So we must add to our earlier solutions the values x = 232 , 233 x = 232, 233 .

Hence our answer is 2 + 46 + 77 + 116 + 232 + 233 = 706 2 + 46 + 77 + 116 + 232 + 233 = \boxed{706} .

Moderator note:

Great Lemma. This is useful in helping us understand linear recurrences which satisfy g n + 2 = g n + 1 + g n g_{n+2} = g_{n+1} + g_n .

A simpler / direct proof uses the characterization of solutions, which must be of the form g n = A α n + B β n g_n = A \alpha^n + B \beta ^n , where A , B A, B are constants and α , β \alpha, \beta are roots of x 2 = x + 1 x^2 = x + 1 .

You have a lovely looking solution here. Even though it is same as "brute" method used by Jimmy K, it looks better.

Mirza Baig - 7 years, 9 months ago

CM do you have a solution along those lines? I tried that at first but I didn't see how to get 233 out of the resulting expression

Matt McNabb - 7 years, 9 months ago

Log in to reply

Solving the recurrence relation g n = g n 1 + g n 2 g_n = g_{n-1} + g_{n-2} , we look for solutions g n = λ n g_n = \lambda^n , leading to the equation λ 2 λ 1 = 0 \lambda^2 - \lambda - 1 = 0 . Thus g n = A α n 1 + B β n 1 g_n = A\alpha^{n-1} + B\beta^{n-1} for n 1 n \ge 1 , where α = 1 2 ( 1 + 5 ) \alpha = \tfrac{1}{2}(1+\sqrt{5}) and β = 1 2 ( 1 5 ) \beta = \tfrac{1}{2}(1-\sqrt{5}) . The conditions g 1 = 1 g_1=1 and g 2 = x g_2=x give A = 1 2 + 1 2 5 ( 2 x 1 ) = 1 5 ( x β ) B = 1 2 1 2 5 ( 2 x 1 ) = 1 5 ( x + α ) \begin{array}{rcl} A & = & \tfrac{1}{2} + \tfrac{1}{2\sqrt{5}}(2x-1) \; = \; \tfrac{1}{\sqrt{5}}(x-\beta) \\ \qquad B &=& \tfrac{1}{2} - \tfrac{1}{2\sqrt{5}}(2x-1) \; = \; \tfrac{1}{\sqrt{5}}(-x+\alpha)\end{array} so g n = 1 5 [ x ( α n 1 β n 1 ) + ( α n 2 β n 2 ) ] n 1 g_n = \tfrac{1}{\sqrt{5}}\big[x(\alpha^{n-1} - \beta^{n-1}) + (\alpha^{n-2} - \beta^{n-2})\big] \qquad n\ge 1 using the fact that α β = 1 \alpha\beta=-1 . But, putting x = 2 x=2 we see that f n = C α n 1 + D β n 1 f_n = C\alpha^{n-1} + D\beta^{n-1} where C = 1 5 ( 2 β ) = 1 5 ( 1 + α ) = 1 5 α 2 D = 1 5 ( 2 + α ) = 1 5 ( 1 β ) = 1 5 β 2 \begin{array}{rcl} C &=& \tfrac{1}{\sqrt{5}}(2-\beta) \; = \; \tfrac{1}{\sqrt{5}}(1+\alpha) = \tfrac{1}{\sqrt{5}}\alpha^2 \\ D & = & \tfrac{1}{\sqrt{5}}(-2+\alpha) \; = \; \tfrac{1}{\sqrt{5}}(-1-\beta) \; = \; -\tfrac{1}{\sqrt{5}}\beta^2 \end{array} so that f n = 1 5 ( α n + 1 β n + 1 ) f_n \; = \; \tfrac{1}{\sqrt{5}}(\alpha^{n+1} - \beta^{n+1}) and hence g n = x f n 2 + f n 3 g_n \; = \; xf_{n-2} + f_{n-3} as required.

This question is a little strange, since the Fibonacci numbers are usually defined as starting 0 , 1 , 1 , 2 , 3 , 5 , 0,1,1,2,3,5,\ldots . If we start with f 1 = 0 f_{-1}=0 and f 0 = 1 f_0=1 , then the above formula for f n f_n is valid for n 1 n \ge -1 , and the above formula relating g n g_n to f n 2 f_{n-2} and f n 3 f_{n-3} is valid for n 2 n \ge 2 , and so Jeremy K. needs no special argument to deal with g 2 g_2 and g 3 g_3 .

Mark Hennings - 7 years, 9 months ago

I do get the induction part, but why was it necessary when you will ultimately have to brute your way through the values?

Shourya Pandey - 5 years, 4 months ago

The values of x can be obtained by listing the terms in the sequence having first term=1 and second term=x.

These are:

1,x,(x+1),(2x+1),(3x+2),(5x+3),(8x+5),(13x+8),(21x+13),(34x+21),(55x+34),(89x+55).

Since, x>=2, we stop at 89x+55.

We then equate the terms (except of course the first term which is 1) to 233 in order to find positive integer values of x.

We obtain the values:

233, 232, 116, 77, 46, 2.

Therefore, the sum of all the possible values of x is 233+232+116+77+46+2=706. :)

Our sequence will be: 1 , x , 1 + x , 1 + 2 x , 2 + 3 x , 3 + 5 x , 5 + 8 x , 8 + 13 x 1,x,1+x,1+2x,2+3x,3+5x,5+8x,8+13x

, 13 + 21 x , 21 + 34 x , 34 + 55 x , 55 + 89 x ,13+21x,21+34x,34+55x,55+89x .

By trial, we find 6 possible values of x that satisfy the given condition: 233,232,116,77,46,2.

The answer is 233+232+116+77+46+2=706

Michael Tong
Sep 2, 2013

The sequence g g is defined as follows: 1 , x , 1 + x , 1 + 2 x , 2 + 3 x , 3 + 5 x , 5 + 8 x 1, x, 1+x, 1+2x, 2+3x, 3+5x, 5+8x , 8 + 13 x , 13 + 21 x , 21 + 34 x , 34 + 55 x , 55 + 89 x 8+13x, 13+21x, 21+34x, 34 + 55x, 55 + 89x
We can stop here because any term above this will necessarily be greater than 233 233 for x 2 x \geq 2 .

For each of these terms of g g , we desire to find a positive integer solution of x x for g n = 233 g_n = 233 . We could brute force it quite easily, giving us values of 233 , 232 , 116 , 77 , 46 , 2 233, 232, 116, 77, 46, 2 whose sum is 706 706 .

I split your sequence into two, so that there is no need to scroll to the right.

Calvin Lin Staff - 7 years, 9 months ago

Computing the first few terms of g g in terms of x x , we have

g 1 = 1 g_1=1

g 2 = x g_2=x

g 3 = 1 + x g_3=1+x

g 4 = 1 + 2 x g_4=1+2x

g 5 = 2 + 3 x g_5=2+3x

g 6 = 3 + 5 x g_6=3+5x

g 7 = 5 + 8 x g_7=5+8x

g 8 = 8 + 13 x g_8=8+13x

g 9 = 13 + 21 x g_9=13+21x

g 10 = 21 + 34 x g_{10}=21+34x

g 11 = 34 + 55 x g_{11}=34+55x

g 12 = 55 + 89 x g_{12}=55+89x .

Note that when x = 2 x=2 , g 12 = 233 g_{12}=233 . Thus, x = 2 \boxed{x=2} is a solution. Since we must have x 2 x \ge 2 , when a > 12 a>12 , then g a g_{a} cannot equal 233 233 . (If x 2 x \ge 2 ). (Note that as x x increases, g 12 g_{12} increases)

If 233 is a term of the sequence g g , then g m g_m must equal 233 for some m m . Thus, we can solve the equations g m = 0 g_m=0 for each m 12 m \le 12 . g 2 = 233 x = 233 g_2=233 \Rightarrow \boxed{x=233} g 3 = 233 1 + x = 233 x = 232 g_3=233 \Rightarrow 1+x=233 \Rightarrow \boxed{x=232} g 4 = 233 1 + 2 x = 233 x = 116 g_4=233 \Rightarrow 1+2x=233 \Rightarrow \boxed{x=116} g 5 = 233 2 + 3 x = 233 x = 77 g_5=233 \Rightarrow 2+3x=233 \Rightarrow \boxed{x=77} g 6 = 233 3 + 5 x = 233 x = 46 g_6=233 \Rightarrow 3+5x=233 \Rightarrow \boxed{x=46} g 7 = 233 5 + 8 x = 233 x = 28.5 ∉ Z g_7=233 \Rightarrow 5+8x=233 \Rightarrow x=28.5 \not \in \mathbb{Z} g 8 = 233 8 + 13 x = 233 x = 225 13 ∉ Z g_8=233 \Rightarrow 8+13x=233 \Rightarrow x=\frac{225}{13} \not \in \mathbb{Z} g 9 = 233 13 + 21 x = 233 x = 220 21 ∉ Z g_9=233 \Rightarrow 13+21x=233 \Rightarrow x=\frac{220}{21} \not \in \mathbb{Z} g 10 = 233 21 + 34 x = 233 x = 106 17 ∉ Z g_{10}=233 \Rightarrow 21+34x=233 \Rightarrow x=\frac{106}{17} \not \in \mathbb{Z} g 11 = 233 34 + 55 x = 233 x = 199 55 ∉ Z g_{11}=233 \Rightarrow 34+55x=233 \Rightarrow x=\frac{199}{55} \not \in \mathbb{Z} g 12 = 55 + 89 x x = 2 g_{12}=55+89x \Rightarrow \boxed{x=2} .

Note that a ∉ Z a \not \in \mathbb{Z} means that a a is not an integer. Since we are looking for integer solutions, these values are to be excluded.

Thus, our solutions are 233 , 232 , 116 , 77 , 46 , 2 233, 232, 116, 77, 46, 2 , and their sum is 706 \boxed{\boxed{706}}

Vishwa Iyer
Sep 3, 2013

Writing out the first 12 12 terms of sequence g g ; 1 , x , x + 1 , 2 x + 1 , 3 x + 2 , 5 x + 3 , 8 x + 5 , 13 x + 8 , 21 x + 13 , 34 x + 21 , 55 x + 34 , 89 x + 55 1, x, x + 1, 2x + 1, 3x + 2, 5x + 3, 8x + 5, 13x + 8, 21x + 13, 34x + 21, 55x + 34, 89x + 55 Because x 2 x \geq 2 , we see that the only way that 233 233 will be a term of sequence g g is when either the 2 2 nd term or every term after it until the 12 12 th term is equal to 233 233 . When 233 233 is equal to the 12 12 th term, we get x = 2 x = 2 . Using the similar method for the 2 2 nd though 11 11 th terms, we get x = 2 , 46 , 77 , 116 , 232 , 233 x = 2, 46, 77, 116, 232, 233 .

2 + 46 + 77 + 116 + 232 + 233 = 706 2 + 46 + 77 + 116 + 232 + 233 = \boxed{706}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...